Impact of human capital and governance in enhancing financial reachability in selected developing countries - Ahsan Aslam Khan; Mohammad Helmi Bin Hidthiir; Zaki Ahmad; Mustazar Mansur (Discover Sustainability)
Abstract The purpose of this study is to investigate how human capital measured by the Education Index, influences financial reachability across lower-, lower-middle-, and upper-middle-income countries. Applying a quantitative approach, the research utilizes panel data analysis from 2011 to 2021 on 89 developing countries, incorporating sources such as the UNDP Human Development Index and the Financial Inclusion Index. The findings highlight that insufficient investment in education can significantly constrain individuals’ capacity to engage with formal financial services, emphasizing the crucial role of financial literacy and skill-building initiatives. The result shows that, while financial accessibility initiatives have made progress, lack of education and weak governance structures continue to hinder financial reach for marginalized populations. Moreover, the study reveals that improvements in governance amplify the benefits of human capital on financial inclusion, creating a more conducive environment for banking institutions and digital financial platforms. This interaction indicates that both structural and policy-level barriers must be addressed concurrently to break the cycle of ineffective financial reach. The outcome of the study implies that targeted educational investment and robust governance measures are indispensable for sustainable economic development. By prioritizing skill enhancement and institutional stability, countries can advance more inclusive financial systems, encourage higher trust in formal financial products, and leverage funds more effectively. Ultimately, the study highlights the strategic importance of comprehensive educational policies and governance reforms as a pathway to achieving broader financial inclusion and enhanced socio-economic welfare.